1994
DOI: 10.1302/0301-620x.76b1.8300689
|View full text |Cite
|
Sign up to set email alerts
|

Soft-tissue expansion before total knee arthroplasty in arthrodesed joints. A report of two cases

Abstract: We report two cases in which arthrodesed knees were revised to total arthroplasties after the use of soft-tissue expanders. Case 1 had had multiple operations on her knee and had been arthrodesed for septic arthritis two years earlier. Case 2 had had knee arthrodesis for severe osteoarthritis 18 years before revision. In both patients, tissue expanders were used to increase the soft tissues available for cover and to help to mobilise the extensor mechanism. The operations were made much easier, and in both pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…In that series, no knee had aseptic loosening (clinically and radiographically) at the final followup. However, one study had a high revision rate for aseptic loosening (18.5% [five of 27 knees]) [16]. We had a low revision rate with a minimum 5-year followup.…”
Section: Discussionmentioning
confidence: 94%
“…In that series, no knee had aseptic loosening (clinically and radiographically) at the final followup. However, one study had a high revision rate for aseptic loosening (18.5% [five of 27 knees]) [16]. We had a low revision rate with a minimum 5-year followup.…”
Section: Discussionmentioning
confidence: 94%
“…In order to reduce the incidence of skin necrosis, skin grafting [3], vascularised gastrocnemius flap [4,5,7] and tissue expanders [4] have been used. Mahomed et al [11] was the first to mention the use of soft-tissue expanders in AD conversion to TKA. They found that the use of soft-tissue expanders helped to provide adequate soft tissue for wound closure in their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors advocate the procedure [5,6,[9][10][11], while others have expressed concern over its efficacy in the presence of the high complication rate [1,2,7,12]. Thus, a systematic review and meta-analyses of the current literature was done, to examine the role of TKA after AD of the knee and assess the clinical outcome, complications, surgical technique, patientrelated outcome measures and methodological quality.…”
Section: Introductionmentioning
confidence: 99%
“…In previously surgically arthrodesed knees, despite anecdotal successful reports [4,11] our own experience with only one success without complications in five knees lead us to believe, like others [1,6], that the risks and benefits of the procedure should be carefully consider before any indication of total knee arthroplasty in this situation.…”
Section: Discussionmentioning
confidence: 80%
“…In knees with multiple incisions, the use of softtissue expansion has been proposed before the knee arthroplasty. The skin expanders help to provide adequate soft tissue for wound closure and the expander under the quadriceps help to mobilize the extensor mechanism [11].…”
Section: Complicationsmentioning
confidence: 99%